Reading Matthew 28:16-20 with Others: How it deconstructs our Western concept of mission - Patte, Daniel (HTS teologiese studies, 2006)
Matthew 28:16-20 is readily read as providing a key teaching about “mission.” Its teaching about mission – going, making disciples of all the nations, baptizing them, teaching them to obey Jesus’ commands – seems simple and clear enough. Yet, this article aims to deconstruct a Western reading of Mt 28:16-20. This is not in order to denounce the legitimacy of such an interpretation. Deconstructing the Western reading is important in order to help us to recognize that there are other equally legitimate and plausible interpretations, and therefore alternate understandings of its teaching about “mission.” In response to the cries of those who suffered from imperialist practices of mission, the article argues that we might want to choose one of the other practices of the mission, one characterized by a respect of the “others” and by a commitment to bringing them a news which will be really good for them.